(untitled) (Marketing Journal, 2026)
Abstract This paper examines how industrial clusters contribute to territorial branding and regional competitiveness from a marketing perspective. The study relies on a literature review and a comparative case analysis of Uzbekistan and selected international examples. Findings suggest that cluster identity, synergy, and differentiation help territories build a unique selling proposition (USP); the “origin of production” mechanism strengthens trust and reputation, while export communications improve cluster brand visibility in international markets. The paper offers practical recommendations for applying the cluster approach to territorial branding and competitiveness policies.Keywords: industrial cluster; territorial brand; competitiveness; branding strategy; positioning; USP; customer loyalty